AN ANALYSIS PHRASE LEVEL TRANSLATION TECHNIQUES APPLIED ON HEROES BACKGROUND IN MOBILE LEGEND: BANG-BANG GAME - Debora Ratulangi, Kristanya (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2018)
This study investigated the translation techniques applied from Mobile Legend: Bang-Bang game and found the purpose of the techniques applied. This research used translation techniques theory from Molina and Albir (2002). The data were popular mobile game Mobile Legend: Bang-Bang game. The source text in English and target text in Indonesian, then analyzed the technique that was applied in heroes background that was translated into Indonesia Language. This study method was qualitative study and this study was a primary research. The result of the analysis was ten techniques are applied in the data. They are reduction, transposition, compensation, modulation, amplification, borrowing-naturalization, particularization, establish equivalent, generalization, calque. The techniques applied have purposes for translation.